Microbial Diversity of Probiotic Potential in the Sediments of Rivers Ganga and Yamuna: A Study Through Metagenomic Approach - Patra, B.; Purohit, H.; Choudhary, S.; Gaur, P.; Behera, B. K. (International Journal of Bio-resource and Stress Management, 2024)
The present study was conducted during the year January, 2016 to December, 2018 in which metagenomics approaches were utilized to identify presence of probiotics species in the river Ganga at Kanpur and Farakka stretches; and stretch of the river Yamuna. It was observed that a huge quantity of probiotic bacterial species are present in these sediments belonging to genus Lactobacillus including L. brevis, L. curvatus, L. helveticus, L. fermentum, L. reuteri, etc; Bacillus including B. clausii, B. circulans, B. subtilis, B coagulans, etc.; Bifidobacterium species including B. animalis, B. bifidum, B. longum, etc. We have found that abundance of Pediococcus pentosaceus was significantly higher in Farakka stretches of Ganga, whereas Pediococcus acidilactici was found in very higher proportion in Kanpur stretch. In this study we present the taxonomic diversity, species of different probiotics and also their relationship with different geographical locations using metagenomic approaches to provide unparalleled insight into probiotics bacteria presents in the river deposits of Ganga and Yamuna. Open Reading Frame (ORF) prediction using CLC genomics, we found one GO-term (GO:0016868) enriched in Molecular Function, 3 GO-terms (GO:0005737, GO:0044424 and GO:0005622) significantly enriched in Cellular Component and one single pathway (00500) is enriched in KEGG Pathways. The STRING functional assignment of Lactobacillus kisonensis-ORF1 encoded protein predicted it as a Heavy metal-associated domain (HMA) and HMA conserved site (copA, zntA). Our sediment metagenomics study able to identify important genes which can be applied for industrial use for the benefit of animal and human welfare.